PEMBERITAAN KEKERASAN DALAM RUMAH TANGGA (KDRT) PADA MEDIA SOSIAL PERSPEKTIF TAFSIR MAQASHIDI (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2024)
The increase in domestic violence cases has become a significant social issue, especially in Muslim-majority countries. Social media, particularly platforms such as Instagram, have become a key tool in building public narratives on the issue of domestic violence from an Islamic perspective. Qur'anic-based narratives on social media are able to generate public solidarity and support for victims, but also pose challenges related to the dissemination of privacy and the potential for slander. The Tafsir Maqasidi approach, which emphasizes the main objectives of sharia (maqashid al-shari'ah) such as the protection of life, honor, and justice, offers an analytical framework to understand this phenomenon contextually. This research uses a qualitative method with a descriptive-analytical approach. Primary data is in the form of relevant Qur'anic verses, such as QS. An-Nisa (4): 135, QS. An-Nur (24): 19, and QS. Ar-Rum (30): 21, as well as the Prophet's traditions. Meanwhile, secondary data includes social media content, tafsir literature, and related articles. The results show that the reporting of domestic violence on social media can be seen as an advocacy effort for victims as long as it fulfills the principles of justice and avoids spreading disgrace. The Qur'anic narrative emphasizes the importance of justice, prohibition of injustice, love in the household, and defense of the oppressed, while maintaining individual privacy. The Tafsir Maqasidi approach emphasizes the need to balance victim advocacy with Islamic ethics that emphasize compassion, justice, and protection of the values of community morality.